Speaking of Inflation: The Influence of Fed Speeches on Expectations - Eleonora Granziera; Vegard H. Larsen; Greta Meggiorini; Leonardo Melosi (CESifo GmbH, 2025)
We examine how speeches by Federal Open Market Committee (FOMC) members, including regional Fed presidents, shape private sector expectations. Speeches that signal rising inflationary pressures prompt both households and professional forecasters to raise their inflation expectations, consistent with Delphic effects. Only professional forecasters respond to Odyssean communications–statements about the Fed's intended policy response–leaving Delphic effects as the dominant channel for households. These household responses are driven by speeches from regional presidents, likely due to greater visibility in regional media coverage. A general equilibrium model, featuring agents who differ in their ability to interpret Odyssean signals, explains this heterogeneity.
Keywords: E31; E58; D83; 330; central bank communication; Delphic; Odyssean; inflation expectations; textual analysis; expectation formation